Dissecting and Reconstructing Matrix in Malignant Mesothelioma Through Histocell-Histochemistry Gradients for Clinical Applications - Balancin, Marcelo Luiz; Baldavira, Camila Machado; Prieto, Tabatha Gutierrez; Machado-Rugolo, Juliana; Farhat, Cecília; Assato, Aline Kawassaki; Velosa, Ana Paula Pereira; Teodoro, Walcy Rosolia; Ab'Saber, Alexandre Muxfeldt; Takagaki, Teresa Yae; Capelozzi, Vera Luiza (Frontiers in Medicine, 2022)
Background. Malignant pleural mesotheliomas (MM) are known for their heterogenous histology and clinical behavior. MM histology reveals three major tumor cell populations: epithelioid, sarcomatoid, and biphasic. Using a dissecting approach, we showed that histochemical gradients help us better understand tumor heterogeneity and reconsider its histologic classifications. We also showed that this method to characterize MM tumor cell populations provides a better understanding of the underlying mechanisms for invasion and disease progression. Methods. In a cohort of 87 patients with surgically excised MM, we used hematoxylin & eosin to characterize tumor cell populations and Movat’s pentachrome staining to dissect the ECM matrisome. Next, we developed a computerized semi-assisted protocol to quantify and reconstruct the ECM in 3D and examined the clinical association between the matricellular factors and patient outcome. Results. Epithelioid cells had a higher matrix composition of elastin and fibrin, whereas, in the sarcomatoid type, hyaluronic acid and total collagen were most prevalent. The 3D reconstruction exposed the collagen I and III that form channels surrounding the neoplastic cell blocks. The estimated volume of the two collagen fractions was 14% of the total volume, consistent with the median estimated area of total collagen (12.05 mm2) for epithelioid MM. Conclusion. Differential patterns in matricellular phenotypes in MM could be used in translational studies to improve patient outcome. More importantly, our data raise the possibility that cancer cells can use the matrisome for disease expansion and could be effectively targeted by anti-collagen, anti-elastin, and/or anti-hyaluronic acid therapies.